Lipid and lipoprotein metabolism in familial combined hyperlipidaemia during treatment of sporadic phaeochromocytoma: a case study. Issue 799 (May 1992) - Winocour, P. H.; Masud, T.; Clark, F.; Cooper, B. G.; Laker, M. F.; Alberti, K. G.
Abstract : Lipid metabolism was evaluated during management of phaeochromocytoma in a 41 year old non-obese post-menopausal women with familial combined hyperlipidaemia. The main effect of the excess catecholamine secretion on lipid metabolism was increased lipolytic activity, lower serum triglyceride and increased HDL cholesterol concentrations, compared with findings following removal of the tumour. Before removal of the tumour, the use of beta blockers alone led to marked deterioration of the hyperlipidaemic state, and combined alpha and beta blockade additionally led to a marked reduction in fat oxidation and lipoprotein lipase activity. Overactivity of the adrenergic system leads to changes in lipid metabolism in phaeochromocytoma. Treatment of the phaeochromocytoma may lead to worsening of hyperlipidaemia pre-existing in such individuals.